THE INFLUENCE OF LEADERSHIP STYLE, COMMUNICATION AND MOTIVATION ON THE PERFORMANCE OF PASAMAN DISTRICT EDUCATION SERVICE EMPLOYEES - Ria Widhia Sari; Endarwita Endarwita; Mai Yuliza; Elondri Elondri (Transpublika Publisher, 2024)
Employees are the backbone of any organization, and their performance directly impacts success. In the education sector, a well-functioning workforce is crucial for student achievement. Effective leadership, clear communication, and motivated employees are all thought to be important for strong performance in organizations. This study is looking into the effect on the performance of Pasaman Regency Education Service Employees of Leadership Style, Communication, and Motivation. 45 staff members from the Pasaman Regency Education Office made up the population of this research. This study sample applies the whole sampling method. Multiple linear regression was used to examine research data acquired by means of a questionnaire distribution approach. Research findings reveal that staff of Pasaman Regency Education Service perform significantly differently depending on their leadership style, partly. With a significance value of 0.551 > 0.05, communication has no appreciable effect on employee performance; motivation similarly has no appreciable effect on performance with a significance value of 0.112 > alpha 0.05. With a significance value of 0.000 alpha 0.05, Leadership Style, Communication, and Motivation concurrently significantly affect the Performance of Pasaman Regency Education Service Employees. From the Coefficient of Determination Test (R2), a value of 0.667 was obtained suggesting that Leadership Style, Communication, and Motivation contribute 66.7% to Employee Performance at the Pasaman Regency Education Office.